2013
DOI: 10.1080/21641846.2013.795085
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome/fibromyalgia: a “stress-adaptation” model

Abstract: Background: A symptom cluster consisting of 'medically-unexplained' chronic fatigue, effort intolerance and widespread pain is a complex and still poorly understood condition. Purpose: To demonstrate the theoretical and clinical value of a biopsychosocially-oriented 'stress-adaptation' model for this multi-symptom illness. Methods: Clinical observation and review of the relevant literature. Results: Symptoms and functional limitations of these patients may reflect a loss of normal physical, mental and emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…It is suggested that over time, chronic stress may lead to a blunted HPA axis response [15]. There is indeed evidence for a lower cortisol response and hypocortisolism in at least a subsample of CFS patients, reflecting a loss of adaptability of the main neurobiological stress response system after a prolonged period of chronic stress [16][17][18].…”
mentioning
confidence: 99%
“…It is suggested that over time, chronic stress may lead to a blunted HPA axis response [15]. There is indeed evidence for a lower cortisol response and hypocortisolism in at least a subsample of CFS patients, reflecting a loss of adaptability of the main neurobiological stress response system after a prolonged period of chronic stress [16][17][18].…”
mentioning
confidence: 99%
“…This cumulative stress leads to dysregulation of the HPA axis, which, in turn, results in stress intolerance and then chronic fatigue. Increasing evidence supports their model, as findings indicate that PC is linked to chronic stress and to changes in the neurobiological functioning implicated in chronic fatigue syndrome (Van Houdenhove, Luyten, & Kempke, 2013). These intriguing findings may also provide important insights that generalize to other illness groups and to healthy samples.…”
Section: Chapter 7 (Molnar Et Al) -14mentioning
confidence: 65%
“…Findings suggest that CPP, fibromyalgia, chronic fatigue syndrome, and asthma are adrenocortical hyporesponsiveness. Several investigated case-control studies have demonstrated that patients with fibromyalgia more often report traumatic childhood experiences such as negligence, maltreatment, or abuse as compared to medically ill or healthy controls (Van Houdenhove et al, 2013). CFS/FM patients (Low & Schweinhardt, 2012) report a history of accumulating psychosocial stress from early childhood.…”
Section: /mentioning
confidence: 99%